Homing of mRNA-Modified Endothelial Progenitor Cells to Inflamed Endothelium - Denis Canjuga; Heidrun Steinle; Jana Mayer; Ann-Kristin Uhde; Gerd Klein; Hans Peter Wendel; Christian Schlensak; Meltem Avci-Adali (MDPI AG, 2022)
Endothelial progenitor cells (EPCs) are one of the most important stem cells for the neovascularization of tissues damaged by ischemic diseases such as myocardial infarction, ischemic stroke, or critical limb ischemia. However, their low homing efficiency in the treatment of ischemic tissues limits their potential clinical applications. The use of synthetic messenger RNA (mRNA) for cell engineering represents a novel and promising technology for the modulation of cell behavior and tissue regeneration. To improve the therapeutic potential of EPCs, in this study, murine EPCs were engineered with synthetic mRNAs encoding C-X-C chemokine receptor 4 (CXCR4) and P-selectin glycoprotein ligand 1 (PSGL-1) to increase the homing and migration efficiency of EPCs to inflamed endothelium. Flow cytometric measurements revealed that the transfection of EPCs with CXCR4 and PSGL-1 mRNA resulted in increased expressions of CXCR4 and PSGL-1 on the cell surface compared with the unmodified EPCs. The transfection of EPCs with mRNAs did not affect cell viability. CXCR4-mRNA-modified EPCs showed significantly higher migration potential than unmodified cells in a chemotactic migration assay. The binding strength of the EPCs to inflamed endothelium was determined with single-cell atomic force microscopy (AFM). This showed that the mRNA-modified EPCs required a three-fold higher detachment force to be released from the TNF-α-activated endothelium than unmodified EPCs. Furthermore, in a dynamic flow model, significantly increased binding of the mRNA-modified EPCs to inflamed endothelium was detected. This study showed that the engineering of EPCs with homing factors encoding synthetic mRNAs increases the homing and migration potentials of these stem cells to inflamed endothelium. Thus, this strategy represents a promising strategy to increase the therapeutic potential of EPCs for the treatment of ischemic tissues.